Patient Safety during ECMO Transportation: Single Center Experience and Literature Review. (22nd February 2021) - Puslecki, Mateusz; Baumgart, Konrad; Ligowski, Marcin; Dabrowski, Marek; Stefaniak, Sebastian; Ladzinska, Malgorzata; Goszczynska, Ewa; Marcinkowski, Pawel; Olasinska-Wisniewska, Anna; Klosiewicz, Tomasz; Pawlak, Aleksander; Zielinski, Marcin; et al.
Abstract : Background . Extracorporeal membrane oxygenation (ECMO) has been proven to support in lifesaving rescue therapy. The best outcomes can be achieved in high-volume ECMO centers with dedicated emergency transport teams. Aim . The aim of this study was to analyze the safety of ECMO support during medical transfer on the basis of our experience developed on innovation cooperation and review of literature. Methods . A retrospective analysis of our experience of all ECMO-supported patients transferred from regional hospital of the referential ECMO center between 2015 and 2020 was carried out. Special attention was paid to transportation-related mortality and morbidity. Moreover, a systematic review of the Medline, Embase, Cochrane, and Google Scholar databases was performed. It included the original papers published before the end of 2019. Results . Twelve (5 women and 7 men) critically ill ECMO-supported patients with the median age of 33 years (2–63 years) were transferred to our ECMO center. In 92% ( n  = 11) of the cases venovenous and in 1 case, venoarterial supports were applied. The median transfer length was 45 km (5–200). There was no mortality during transfer and no serious adverse events occurred. Of note, the first ECMO-supported transfer had been proceeded by high-fidelity simulations. For our systematic review, 68 articles were found and 22 of them satisfied the search criteria. A total number of 2647 transfers were reported, mainly primary (90%) and as ground transportations (91.6%). A rate of adverse events ranged from 1% through 20% but notably only major complications were mentioned. The 4 deaths occurred during transport (mortality 0.15%). Conclusions . Our experiences and literature review showed that transportation for ECMO patients done by experienced staff was associated with low mortality rate but life-threatening adverse events might occur. Translational simulation is an excellent probing technique to improve transportation safety.